Cabbage aphid Brevicoryne brassicae Linnaeus (Insecta: Hemiptera: Aphididae)1 - Harsimran Kaur Gill; Harsh Garg; Jennifer L. Gillett-Kaufman (EDIS)
Cabbage aphids cause significant yield losses to many crops of the family Brassicaceae, which includes the mustards and crucifers. It is important to have a comprehensive understanding of this pest and its associated control measures so that its spread and damage can be prevented. This 5-page fact sheet was written by Harsimran Kaur Gill, Harsh Garg, and Jennifer L. Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, October 2013.